2023
DOI: 10.1039/d2sc06409j
|View full text |Cite
|
Sign up to set email alerts
|

A stronger acceptor decreases the rates of charge transfer: ultrafast dynamics and on/off switching of charge separation in organometallic donor–bridge–acceptor systems

Alexander J. Auty,
Paul A. Scattergood,
Theo Keane
et al.

Abstract: The rate of intersystem crossing increases, whilst the rates of charge separation and recombination decrease in donor–CC–Pt–CC–acceptor systems with a stronger electron acceptor – as revealed by fluorescence upconversion and ultrafast IR methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 74 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…The experimental spectrum recorded in DCM is shown as an inset for comparison with the calculated spectrum. The main features of the poorly resolved experimental spectrum are well reproduced at this level of broadening, with one intense band between 300 and 400 nm, showing a shoulder at about 325 nm and a slightly red-shifted broad band between 480 and 670 nm. This band is attributed to the charge transfer from the bridge to the acceptor, so-called L B L A CT, that describes the S 0 → S 3 and S 0 → S 4 electronic transitions, the electronic densities of which are represented in Scheme .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The experimental spectrum recorded in DCM is shown as an inset for comparison with the calculated spectrum. The main features of the poorly resolved experimental spectrum are well reproduced at this level of broadening, with one intense band between 300 and 400 nm, showing a shoulder at about 325 nm and a slightly red-shifted broad band between 480 and 670 nm. This band is attributed to the charge transfer from the bridge to the acceptor, so-called L B L A CT, that describes the S 0 → S 3 and S 0 → S 4 electronic transitions, the electronic densities of which are represented in Scheme .…”
Section: Resultsmentioning
confidence: 96%
“…However, quantum simulations beyond the Born−Oppenheimer (BO) approximation considering the interplay and coupling between the active electronic excited states and the nuclear vibrational state manifold are required to model the nonadiabatic dynamics in real time and to decipher the spin-vibronic mechanism underlying the ultrafast competitive excited state decays. 27−31 Inspired by our recent rationalization of the ultrafast excited state decay in [Pt(dpybMe)Cl] (dpyb = 2,6-di(2-pyridyl-(benzene))), reference molecule for square planar Pt(II) cyclometalated complexes, we propose here a thorough exploration of the spin-vibronic mechanism at work in a DBA system recently investigated by Weinstein et al 26 bearing a PTZ donor group associated with a Pt(II) trans-acetylide bridge conjugated with a naphthalene-diimide (NDI) acceptor (Scheme 1). This work based on transient absorption, TRIR, and upconversion fluorescence spectroscopies supported by TD-DFT calculations illustrates the difficulty at rationalizing the behavior, sometimes counterintuitive, in similar complexes with modified acceptor groups A, namely, NAP of NDI.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many photoactive structures also incorporate a bridging group or groups between the donor and acceptor moieties, which can subsequently affect the excited state properties and electron and or energy transfer processes. ,, For example, thiophene units are frequently found in polymers as they are well known for their conducting ability, improving π-conjugation and facilitating charge transfer. Thiophenes have also been successfully incorporated into donor–acceptor dyes and have been shown to red-shift as well as increase the intensity of the charge-transfer transition in both organic and inorganic systems. ,,, Ethynyl bridges have also been shown to increase donor–acceptor communication in a similar manner, providing a means of connecting different moieties in a rigid, planar geometry due to the sp-hybridized carbons. , Robson et al studied a family of Ru­(II) terpyridine complexes with triphenylamine (TPA) donors connected through ethynyl and thiophene bridges . They found that the lowest energy state was ILCT in nature and was red-shifted by the inclusion of both ethynyl and thiophene groups.…”
Section: Introductionmentioning
confidence: 99%